Risks and Benefits of Swaddling Healthy Infants: An Integrative Review. Issue 4 (July 2017) - Nelson, Antonia M.
Abstract: Background: Swaddling has been practiced since antiquity; however, there is controversy about its safety. Objectives: The purpose of this review is to update and build upon previous reviews and synthesize evidence on risks and benefits of swaddling in healthy-term, near-term, or older infants. Data Sources: MEDLINE (1960–May 13, 2016) and CINAHL (1963–May 13, 2016) searches were conducted, relevant articles retrieved, and citation lists reviewed for other references. Synthesis Methods: A table summarizes study details. Selected older references and supporting literature are integrated into the synthesis to provide context. Results: Swaddling calms infants and promotes sleep, but it is equally or less effective than other nonpharmacological methods in managing pain. There may be a slight risk for sudden infant death syndrome associated with supine swaddling, although the impact of confounding variables is unclear. Early skin-to-skin contact supports early breastfeeding, but swaddling does not have a negative impact on breastfeeding long term. Swaddling tightly around the hips is strongly associated with developmental dysplasia of the hip. More research is needed on the impact of swaddling on pain in term infants, infant vital signs, arousal thresholds, and a possible association between swaddling, vitamin D deficiency, and acute lower respiratory tract infection. Limitations: The number of studies was small, with few randomized control trials, and researchers used different definitions of swaddling. Conclusions: If a few precautions are taken, such as swaddling securely to minimize risk of unwrapping, avoiding overheating, placing infants to sleep supine, and discontinuing swaddling when infants first show signs of rolling over, swaddling presents minimal risk. Clinical Implications: Maternity and neonatal nurses should model swaddling practices based on the evidence and promote informed decision-making among infant caregivers. Abstract : Swaddling has been practiced for ages; however, there is controversy about its safety. This integrative review covers recent evidence on various issues about infant swaddling so nurses can offer accurate advice to parents and infant caregivers.